Four Decades of Clinical Liver Transplantation Research: Results of a Comprehensive Bibliometric Analysis. Issue 10 (14th July 2022) - Jiang, Decan; Ji, Tengfei; Liu, Wenjia; Bednarsch, Jan; Selzner, Markus; Pratschke, Johann; Lurje, Georg; Cao, Tiansheng; Brüggenwirth, Isabel M.A.; Martins, Paulo N.; Arke Lang, Sven; Peter Neumann, Ulf; et al.
Abstract : Background: Nearly 40 y have passed since the 1983 National Institutes of Health Consensus-Development-Conference, which has turned liver transplantation (LT) from a clinical experiment into a routine therapeutic modality. Since‚ clinical LT has changed substantially. We aimed to comprehensively analyze the publication trends in the most-cited top-notch literature in LT science over a 4-decade period. Methods: A total of 106 523 items were identified between January 1981 and May 2021 from the Web of Science Core Collection. The top 100 articles published were selected using 2 distinct citation-based strategies to minimize bias. Various bibliometric tools were used for data synthesis and visualization. Results: The citation count for the final dataset of the top 100 articles ranged from 251 to 4721. Most articles were published by US authors (n = 61). The most prolific institution was the University of Pittsburgh (n = 15). The highest number of articles was published in Annals of Surgery, Hepatology, and Transplantation ; however, Hepatology publications resulted in the highest cumulative citation of 9668. Only 10% of the articles were classified as evidence level 1. Over 90% of first/last authors were male. Our data depict the evolution of research focus over 40 y. In part, a disproportional flow of citations was observed toward already well-cited articles. This might also project a slowed canonical progress, which was described in other fields of science. Conclusions: This study highlights key trends based on a large dataset of the most-cited articles over a 4-decade period. The present analysis not only provides an important cross-sectional and forward-looking guidance to clinicians, funding bodies, and researchers but also draws attention to important socio-academic or demographic aspects in LT. Abstract :